Liquid Ecstasy: Néstor Perlongher and Visionary Poetry in Latin America (Revista de Crítica Literaria Latinoamericana, 2012)
This article has two parts: in the first one, considering other studies that have established bonds with some mystical traditions, I propose the study of a possible visionary tendency in Latin American poetry. In the second one, I analyze the final stage of the poetry of Argentinean Néstor Perlongher, produced while participating in Santo Daime's rimais in Brazil. For that purpose, I compare the liquid and colorful characteristics of his writing with images from diferents contexts, such as psychedelia, the huicholes, medieval mysticism and sufism.
Keywords: Néstor Perlongher; Ayahuasca; Psychedelia; Medieval Mysticism; Sufism; Visionary Poetry